Does perceived normativity of intergenerational contact enhance the effects of imagined intergenerational contact?. (October 2021) - Fowler, Craig; Harwood, Jake
Two experiments investigated effects of imagined intergroup contact (IIC) on young adults' stereotypical perceptions of and intention to communicate with older adults. Both studies tested a third-person variant of IIC (extended IIC). Also, Study 1 explicitly manipulated the perceived normativity of intergenerational contact by providing relevant information, and Study 2 implicitly manipulated perceived normativity via task repetition. In Study 1, IIC (including extended IIC) had few effects. However, the explicit norms manipulation changed perceptions of norms, which improved perceptions of older adults and increased desire for future intergenerational communication. In Study 2, some forms of IIC reduced intergenerational anxiety, which translated into more positive intergenerational perceptions. Moreover, repeated IIC had positive effects on intergenerational perceptions that were mediated by perceptions of norms and that persisted for a week. We advocate more attention to the effect of IIC on norms, and to the conditions under which IIC works (and does not).